An In-Vitro Study to Find the of Frequency ofMB2 Canal in Permanent Maxillary Molars (Academia Journal of Medicine, 2024)
Present in-vitro research conducted to find out the  frequency of second mesiobuccal canals in permanent  maxillary molars. Eighty extracted, intact maxillary  permanent molars were selected for the present study.  Following that, a slow-speed diamond disc was used to  divide the occlusal sections of the crowns at the cement enamel junction. Using a safe-end diamond bur,  overhanging dentin that covered the canal orifices was  removed to allow straight line visibility. Under an x8  magnification, the teeth were photographed from their  occlusal side. Result showed that the first and second  maxillary molars, MB2 canals were found in 70% and 55%,  respectively. In conclusion it is crucial during endodontic procedures on maxillary molars to cautiously check pulpal  floor to detect any "extra" canals, notably the second  mesiobuccal canal, by scraping away the constrictive  dentin above the orifices.
Keywords: Endodontic treatment; Maxillary Molar; MB2